Associativism and extensionism: a proposal for ecotourism and reproduction of productive backyards Caratateua island, Belém–PA - Oliveira, Rita Denize de; Silva, José Augusto Lopes da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Caratateua Island comprises the insular portion of the metropolitan region of Belém-Pará. Despite the historical abandonment of the State, demonstrated in the low level of basic sanitation and difficulties in the supply of potable water and a precarious sewage network, limited availability of high schools and only one health center to serve the people of the island, the place ends up being a refuge for the population excluded by urban reform projects, such as the macro-drainage of the hydrographic basins of Belém, for example, in addition to receiving families who migrate from other interior cities and Ilha do Marajó. However, the island is reference for Environmental Education, through sustainable practices dissemination by the Fundação Escola Bosque Professor Eidorfe Moreira, housing popular cultural events such “cordão de pássaros juninos” and “boi bumbá” and festivals such as “Círio de Nossa Senhora da Conceição” and festivities of Iemanjá. Another specificity of the island is a strong political activism that manifests itself in the formation of associations with different purposes, from religious freedom, ancestry, valorization of rites and recovery of knowledge, to purposes involving human rights, rehabilitation, reintegration into the market for disabled people, agroecology, local development and food security as proposed by the Beneficent Association of Disabled and Reduced Mobility People of Pará, which constitutes a proposition to face the post-pandemic crisis in insular areas and is the main theme of this article.